Effects and mechanisms of digitalization to enhance the resilience of the hog breeding industry: evidence from China - Hua, Junguo; Ma, Chunhui; Li, Wei; He, Zejun; Zhu, Panpan (Frontiers in Sustainable Food Systems, 2024)
Introduction With the rapid development of digital agriculture, digitalization has gradually become a key factor affecting the resilience of China’s pig farming industry. Methods From both the test results and the theoretical point of view, the individual fixed-effect model is more suitable for this paper’s study. Therefore, based on the panel data of 31 provinces in China from 2011 to 2022, this study constructs an individual fixed-effect model to examine how digitization affects the resilience of China’s pig farming industry. Results and discussion The findings indicated that digitization significantly enhanced the resilience of China’s hog breeding industry, especially in potential growth areas. Improving breeding technology and scale is a crucial avenue for digitalization to bolster the industry’s resilience. Digitalization exerts a double threshold effect on the industry’s resilience, with its promotional impact only realized within a specific range. The article proposes policy suggestions, such as strengthening infrastructure construction and giving play to regional advantages.